EVALUATING THE BENEFITS OF PROVIDING ARCHIVED ONLINE LECTURES TO IN-CLASS MATH STUDENTS - Cascaval, Radu C.; Fogler, Kethera A.; Abrams, Gene D.; Durham, Robert L. (Online Learning, 2008)
The present study examines the impact of a novel online video lecture archiving system on in-class students enrolled in traditional math courses at a mid-sized, primarily undergraduate, university in the West. The archiving system allows in-class students web access to complete video recordings of the actual classroom lectures, and sometimes of lecture notes, shortly after the in-class sessions are completed. The data collection for evaluating the impact of this archiving system was designed through focus groups, and consequently, obtained using a customized web survey. Survey questions targeted areas of potential impact, such as changes in attitudes and behaviors (such as study habits), changes in the dynamics of professor-student relationship, and the overall student performance enhancement. The results indicate that the presence of the archived video lectures and lecture notes adds significant value to the learning process with notable improvements in the perceived student performance and overall experience in the class.